2013
DOI: 10.1080/02755947.2013.790861
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Monitoring of Threatened Chinook Salmon Populations: Estimating Introgression of Nonnative Hatchery Stocks and Temporal Genetic Changes

Abstract: Conservation efforts aimed at Pacific salmon (Oncorhynchus spp.) populations have frequently utilized artificial propagation in an attempt to increase fish abundance. However, this approach carries the risk of unwanted changes in the genetic characteristics of the target population and perhaps others that might incidentally be affected. We used genetic monitoring techniques to estimate the amount of introgression that has occurred from nonnative hatchery stocks into native populations and to determine the exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Previous analyses have suggested that hatchery fish have had minimal influence on genetic diversity in this ESU despite high numbers of hatchery strays on spawning grounds (Van Doornik et al. , , Matala et al. ).…”
Section: Discussionmentioning
confidence: 88%
“…Previous analyses have suggested that hatchery fish have had minimal influence on genetic diversity in this ESU despite high numbers of hatchery strays on spawning grounds (Van Doornik et al. , , Matala et al. ).…”
Section: Discussionmentioning
confidence: 88%
“…Empirical studies of the spatiotemporal relationship between N and N b among populations spanning a large gradient of population sizes are rare (Van Doornik et al . ; Perrier et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Total hatchery releases of Chinook salmon into the Pacific Ocean increased substantially during the 1970s and somewhat during the 1980s and have since been declining (Figure ). Hatchery‐reared fish could alter the age‐size structures of populations coast‐wide via two mechanisms: direct effects on competition for resources in the ocean (Ruggerone & Goetz, ), or as a consequence of selective breeding and introgression of selected genotypes into wild populations, especially small populations in close geographic proximity to hatcheries (Van Doornik et al., ). The selective breeding of Chinook salmon in hatcheries might have produced faster‐growing fish that attain larger sizes during the first two or 3 years in the ocean but do not reach larger maximum sizes compared to wild fish.…”
Section: Discussionmentioning
confidence: 99%